Adsorption of dimers on heterogeneous surfaces: Scaling behavior for the adsorption isotherms - González, José Eduardo (2002)
The localized monolayer adsorption of homonuclear dimers on heterogeneous surfaces with simple topographies is analyzed by combining theoretical modeling and Monte Carlo (MC) simulations. The heterogeneous surfaces are represented by lattices with two kinds of sites, the so-called bivariate heterogeneous surface. Shallow and deep sites with energies (S) and (D), respectively, form l × l patches distributed at random or in chessboard-like ordered domains on two-dimensional square, honeycomb and triangular lattices. The adsorption process is monitored by following the adsorption isotherms. The scope of the present work is to determine, via MC simulation and a theoretical model, the general properties of the adsorption of non-interacting dimers on bivariate surfaces with a characteristic correlation length, l. These findings are discussed for the determination of the energetic topography of the surface, from adsorption measurements.